آراء متعلمي اللغة الإنجليزية كلغة أجنبية حول أهمية مختبرات تعلم اللغة الإنجليزية في تحسين مهارات المحادثة - القحواش, Aisha; موسي, Omaima (مجلة الاصالة, 2026)
This study investigates EFL university students' perceptions regarding the impact of language laboratories on their speaking skills at Abu Issa College of Education, University of Zawiya. Using a quasi-experimental approach involving surveys and pre/post-tests, the research analyzed students' attitudes and performance. Results indicate a significantly positive attitude toward physical language labs, with most participants asserting that these facilities enhance pronunciation, fluency, and overall communicative competence. Furthermore, the findings suggest that language labs provide a low-anxiety environment that fosters confidence. Despite these benefits, students identified challenges such as limited accessibility and technical issues. The study concludes that language labs are vital for EFL proficiency and recommends their systematic integration into the curriculum .